2017
DOI: 10.1002/acm2.12185
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning of a PTW 34070 large‐area plane‐parallel ionization chamber for small field megavoltage photon dosimetry

Abstract: PurposeThis study investigates a large‐area plane‐parallel ionization chamber (LAC) for measurements of dose‐area product in water (DAP w) in megavoltage (MV) photon fields.MethodsUniformity of electrode separation of the LAC (PTW34070 Bragg Peak Chamber, sensitive volume diameter: 8.16 cm) was measured using high‐resolution microCT. Signal dependence on angle α of beam incidence for square 6 MV fields of side length s = 20 cm and 1 cm was measured in air. Polarity and recombination effects were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…As shown in this work, the heterogeneity correction factor for BPC2 is 0.978, which means that the DAP directly measured by BPC2 would be subject to a 2.2% systematic deviation if the chamber response heterogeneity was ignored. This systematic deviation is consistent with that reported in recent publications …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…As shown in this work, the heterogeneity correction factor for BPC2 is 0.978, which means that the DAP directly measured by BPC2 would be subject to a 2.2% systematic deviation if the chamber response heterogeneity was ignored. This systematic deviation is consistent with that reported in recent publications …”
Section: Discussionsupporting
confidence: 94%
“…This over‐response may be due to the fact that the size of the guard ring is actually larger by 0.4 mm than the specified value of 40.8 mm. Kupfer et al also observed a similar overresponse at the edge of BPC, and argue that this is due to insufficient width of the guard ring. When the BPC is calibrated using a large field, this over‐response must be taken into account.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations